The Effect of Insulin Injection Time on Blood Glucose Levels 2 Hours After Meals in Type II Diabetes Mellitus Patients at Grandmed Hospital Lubuk Pakam - an, Pitriani; Hayati, Kardina; Tamba, Elsa Sumitra; Sitepu, Abdi Lestari (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Increased blood sugar levels in the body are one of the characteristics of type II diabetes mellitus. Controlling blood sugar levels can be done by checking blood glucose levels. This study aims to analyze blood glucose levels two hours after eating with insulin injection 11-20 minutes before eating and blood glucose levels two hours after eating with insulin injection 0-10 minutes after eating. This study uses a quantitative method with a Cross-Sectional design. Data were collected using a total sampling technique, with a sample size of 18 respondents. The results of the statistical test showed a probability of 0.001, which is smaller than the significance level (? = 0.05). This shows a significant difference between blood glucose levels two hours after eating in patients who received insulin injections 11-20 minutes before eating (Pretest) and those who received insulin injections 0-10 minutes after eating (Posttest). Thus, it can be concluded that the time of insulin injection affects blood glucose levels two hours after eating in patients with type II diabetes mellitus at Grandmed Hospital Lubuk Pakam.